A Scientometric Study of Quality Assessment and Higher Education - B. S., Prashantha; Dorairajan, M.; U.S., Vijayaraj Kumar; Srinivasaragavan, S. (The Scientific Temper, 2025)
This study evaluates the research publication of Quality Assessment and Higher Education for the period of 2015-2025. The purpose of this study is to analyse the research outcome on QA & HE using scientometrics tools and techniques such as Annual research output by the researcher, kinds of documents, top ten authors, affiliation wise, country wise distribution papers, journal wise and Language wise on QA & HE. The study revealed that the highest number of research papers was published in the year 2025 with 1270(14.49%). The top three journals based on the number of publications were BMC Medical Education with 206 (12.05%), Plos one with 163(9.54%) and Sustainability with 137(8.02%). The majority of publications were articles with 7015 (80.02%) chosen by the researcher. Zhang, Y. with 30 (13.51%) publications and share the 1st place. The top affiliation is the University of Toronto, Canada with 197 (12.20%) publications. The most productive country was The United States of America (2653) publications. “Quality” is the most frequent word with 1563 occurrences from 2015 to 2025. This study will be helpful for further research in the field of scentomentrics, library professionals who are working in higher education and quality assessment.